2022
DOI: 10.1007/s00018-022-04363-6
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor networks in trophoblast development

Abstract: The placenta sustains embryonic development and is critical for a successful pregnancy outcome. It provides the site of exchange between the mother and the embryo, has immunological functions and is a vital endocrine organ. To perform these diverse roles, the placenta comprises highly specialized trophoblast cell types, including syncytiotrophoblast and extravillous trophoblast. The coordinated actions of transcription factors (TFs) regulate their emergence during development, subsequent specialization, and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 131 publications
0
36
0
Order By: Relevance
“…Pathways of nutrient transport and mammary gland development were also identified (Figure 4D). In EVT, pathways such as the epithelial to mesenchyme transition pathway, epithelial development and differentiation, extracellular matrix organization were identified as previously described (Illsley et al, 2020;Papuchova and Latos, 2022), which were associated with the invasive activities of EVT (Figure 4D; Supplementary Table S5).…”
Section: Spatial Regulatory Activity Of Transcription Factors In Villimentioning
confidence: 64%
“…Pathways of nutrient transport and mammary gland development were also identified (Figure 4D). In EVT, pathways such as the epithelial to mesenchyme transition pathway, epithelial development and differentiation, extracellular matrix organization were identified as previously described (Illsley et al, 2020;Papuchova and Latos, 2022), which were associated with the invasive activities of EVT (Figure 4D; Supplementary Table S5).…”
Section: Spatial Regulatory Activity Of Transcription Factors In Villimentioning
confidence: 64%
“…( 49 ) reported that knockdown of ribosomal protein L39 ( RPL39 ) inhibited the proliferation, migration, and invasion of trophoblast cells in vitro . APO was closely related to abnormal biological function of trophoblasts, since trophoblast cells were vital to placental and fetus development ( 50 , 51 ). Therefore, the expression of SEZ6 and LPAR4 might play potential pathogenic role in APO.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted August 3, 2022. ; https://doi.org/10.1101/2022.08.02.502490 doi: bioRxiv preprint lineage-specific expression (Papuchova and Latos 2022). Starting with in-depth inspection of the primate-specific MER41 family followed by comprehensive analysis on candidate TFs and the entire ERVome, this study aims to better understand the regulation and function of ERV-associated enhancers in the human trophoblast regulatory network.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that dozens of ERV families – many are primate-specific – create numerous human placental enhancers (Sun et al 2021), yet the underlying regulatory mechanism remains to be explored. Furthermore, it is also highly desirable to delineate how ERV-associated enhancers participate in the trophoblast gene network, which is under the cooperative regulation of many TFs – including some with lineage-specific expression (Papuchova and Latos 2022). Starting with in-depth inspection of the primate-specific MER41 family followed by comprehensive analysis on candidate TFs and the entire ERVome, this study aims to better understand the regulation and function of ERV-associated enhancers in the human trophoblast regulatory network.…”
Section: Discussionmentioning
confidence: 99%